Profitability of Small Scale Broiler Production in Some Selected Areas of Mymensingh - Rana, KMAAM; Rahman, MS; Sattar, MN (Progressive Agriculture, 2013)
This study aimed to determine the cost, return, and profitability of broiler production in some selected areas of Mymensingh district. It was mainly based on primary data which were collected through face to face interview from the respondents of broiler production during the month of December, 2011. Selected samples consisted of 30 broiler farm owners selected by using purposive sampling technique. For the analysis of data, tabular and production function techniques were used. This study estimated the average cost of raising broiler to be Tk. 8,35,910.65 per farm per year. It was found that the variable cost per farm per year stood at Tk. 8,23,735.93 which accounted for 98.54 percent of total cost. The total fixed cost per farm per year accounted to Tk. 14,041.66. It is evident from the study that the gross return per farm per year stood at Tk. 10,78,022.39. The net return per farm per year was calculated at Tk. 2,42,111.47. The findings revealed that broiler production was a profitable enterprise. Cobb-Douglas production function was also applied to explore the specific effect of the factors on broiler production. It was observed that most of the included variables had significant impact on broiler production. Out of six variables included in the regression, four variables (i.e., feed cost, cost of day-old chick, labour cost and litter cost) had significant positive impact on return. This study also identified some problems in the production of broiler in the study area. Finally, based on the findings of the study, some recommendations were made for the development of broiler production in Bangladesh. DOI: http://dx.doi.org/10.3329/pa.v23i1-2.16568 Progress. Agric. 23(1 & 2): 101 109, 2012